Successful Advanced Practice Nurse Role Transition A Structured Process to Developing Professional Identity through Role Transition - Kidner, Maria; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book starts by discussing the APN role and the roles of the APN nurses in specific countries and around the globe. It then analyzes the concept of role transition to provide a basis for exploring and developing professional identity, and describes the APN roles of educator, communicator, advocate, mentor, team member and leader to facilitate role transition and professional identity formation. The transition from registered nurse to advanced practice nurse is typically a dramatic life event. Providing insights into role transition, role ethics, and developing a professional identity, the book encourages readers to explore issues that help ensure that the transition is successful. This unique book allows readers to gain the skills to help them negotiate role transition through the development of their professional identity. It describes precise steps for developing personal values, visions, and mission and goal statements; communication skills to enhance authority, accountability, and responsibility of all parties; team-working skills to improve outcomes; and processes for self-understanding. This book is intended for students in APN programs, new graduates, nurses changing roles where there is role transition confusion, and APNs seeking to understand their professional identity and /or gain insights into the multiple roles of the APN.
Keywords: Nursing; Nursing; Nurse Clinicians; Nurse Practitioners; Nurse Midwives